Determinant Spiritual School Well-Being Factors of Happiness and Job Satisfaction for Teachers in Central Kalimantan - Fransiskus Janu Hamu; Donatus Wea; Honorata Ratnawati Dwi Putranti (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This study aims to analyze the value of happiness and job satisfaction of teachers in Central Kalimantan. Besides that, this study will examine the effect of work for happiness, job satisfaction, the meaning of work, and work engagement on job satisfaction and happiness. The quantitative approach used AMOS software to test the hypothesis by taking a sample of 156 teachers in Central Kalimantan. The research instrument used a measurement scale questionnaire in this study. This study's results indicated that reading and writing literacy could develop prophetic character education for elementary school students.When teachers feel satisfied and happy in their jobs, they tend to pay more attention to the quality of their work and are more committed to students and the institution and have higher retention rates, generally being more productive. The meaning of all this is that teachers have strategic value by improving the quality of work and being more committed to educational institutions.